الفقيه و السلطة في السودان الغربي من القرن 2ه-9ه - قعيد,بدرة; فريوة,ليلى (University of Eloued جامعة الوادي, 2024)
حتما يمكن القول أن دور الفقيه في السلطة في السودان الغربي فتحت آفاقا جديدةلفهم تطور الفكر السياسي الاسلامي وتطبيقاته وتعزز من أهمية البحث المستمر في هذه المجالات لفهم الماضي بشكل أفضل والاستفادة منه في بناء مستقبل أكثر استقرار وعدلا. Inevitably, it can be said that the role of the jurist in power in western Sudan has opened new horizons for understanding the development of Islamic Political Thought and its applications and enhances the importance of continuous research in these areas to better understand the past and benefit from it in building a more stable and just future
Keywords: western Sudan; authority; Al-Faqih; السودان الغربي; السلطة; الفقيه